Renewable energy perspectives in the frame of Turkey's and the EU's energy policies - YILMAZ, MUSTAFA (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
Renewable energy as one of the current and substantial issue needs to be investigated in terms of political outlook. So the researches on renewable energy policies under the energy policies of different countries are necessary. The emergence of renewable energy policy was the 20th century but it gained momentum in 21st century. The realization of the polluting nature of the petroleum products, their negative environment effects and the assumptions about the future of non-renewable energy sources were the driving forces behind these politics. The European Union in these conditions tries to play pioneer role. Turkey on the other hand as a candidate country has to harmonize its policies with the Union's. In this context, objective of this work is to examine the EU and Turkey's renewable energy policies, make a comparison and as a sustainability of Turkish renewable energy policy construct a future projection in short, medium and long terms. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Renewable energy policy; The European Union; Turkey; SUSTAINABLE ENERGY; CONSUMPTION